Host plant-mediated effects on Buchnera symbiont: implications for biological characteristics and nutritional metabolism of pea aphids (Acyrthosiphon pisum) - Liu, Hui-ping; Yang, Qiao-yan; Liu, Jing-xing; Haq, Inzamam Ul; Li, Yan; Zhang, Qiang-yan; Attia, Kotb A.; Abushady, Asmaa M.; Liu, Chang-zhong; Lv, Ning (Frontiers in Plant Science, 2023)
The pea aphid, Acyrthosiphon pisum (Harris), is a typical sap-feeding insect and an important worldwide pest. There is a primary symbiont-Buchnera aphidicola, which can synthesize and provide some essential nutrients for its host. At the same time, the hosts also can actively adjust the density of bacterial symbiosis to cope with the changes in environmental and physiological factors. However, it is still unclear how symbionts mediate the interaction between herbivorous insects' nutrient metabolism and host plants. The current study has studied the effects of different host plants on the biological characteristics, Buchnera titer, and nutritional metabolism of pea aphids. This study investigated the influence of different host plants on biological characteristics, Buchnera titer, and nutritional metabolism of pea aphids. The titer of Buchnera was significantly higher on T. Pretense and M. officinalis, and the relative expression levels were 1.966±0.104 and 1.621±0.167, respectively. The content of soluble sugar (53.46±1.97µg/mg), glycogen (1.12±0.07µg/mg) and total energy (1341.51±39.37µg/mg) of the pea aphid on V. faba were significantly higher and showed high fecundity (143.86±11.31) and weight (10.46±0.77µg/mg). The content of total lipids was higher on P. sativum and T. pretense, which were 2.82±0.03µg/mg and 2.92±0.07µg/mg, respectively. Correlation analysis found that the difference in Buchnera titer was positively correlated with the protein content in M. officinalis and the content of total energy in T. pratense (P < 0.05). This study confirmed that host plants not only affected the biological characteristics and nutritional metabolism of pea aphids but also regulated the symbiotic density, thus interfering with the nutritional function of Buchnera. The results can provide a theoretical basis for further studies on the influence of different host plants on the development of pea aphids and other insects.